The production of singular- and plural-dominant nouns in Dutch - Beyersmann, E.; Dutton, E.; Amer, S.; Schiller, N.; Biedermann, Britta-Andrea (Routledge, 2015)
The role of number dominance (singular vs. plural) in word production has revealed contrasting results in Dutch and English. Here, we compared the production of Dutch regular plural forms that are more frequent than their stems (plural-dominant plurals) to plurals that are less frequent than their stems (singular-dominant plurals) in a spoken picture-naming paradigm. Moreover, the role of inflectional entropy during spoken word production was assessed. The results revealed that singular-dominant singulars were produced significantly faster and more accurately than their corresponding plurals, independently of inflectional entropy. However, the production of plural-dominant plurals and singulars was modulated by inflectional entropy, and a plural disadvantage only found if the inflectional variants were not uniformly distributed. Critically, uniformly distributed variants showed a plural advantage in this condition. Our findings suggest that singular-dominant and plural-dominant plurals are processed differently, which we discuss in the context of morphological processing theories in spoken language production.